2014
DOI: 10.1002/2013jd021286
|View full text |Cite
|
Sign up to set email alerts
|

Decadal change of South China Sea tropical cyclone activity in mid‐1990s and its possible linkage with intraseasonal variability

Abstract: This study focuses on the decadal variability of tropical cyclone (TC) activity over the South China Sea (SCS) since the 1970s and its possible cause behind. It is found that TC activity over the SCS experiences a significant decadal change around the mid-1990s. Compared to the period from the 1970s to the early 1990s, the number of TCs formed in the SCS remarkably increases from the mid-1990s through the 2000s. In particular, this change of TC genesis is closely related to a decadal shift in atmospheric intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 57 publications
3
41
1
Order By: Relevance
“…This observation suggests that the largescale environmental change associated with SVD1 in 1976-1977 was partially offset by the effect of SVD2. In addition to the large-scale factors, the interdecadal variation in TC activity in the WNP was also affected by other processes, such as intraseasonal oscillations (Hsu et al 2008;Kim et al 2008;Ha et al 2014), which cannot be measured using the interdecadal time scale. The interdecadal change in TC activity in other periods, such as the increase in TC activity in the ENP during 1976-1977 and the increase in TC activity in the WNP during the late 1980s, might be attributable to other processes not currently under investigation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This observation suggests that the largescale environmental change associated with SVD1 in 1976-1977 was partially offset by the effect of SVD2. In addition to the large-scale factors, the interdecadal variation in TC activity in the WNP was also affected by other processes, such as intraseasonal oscillations (Hsu et al 2008;Kim et al 2008;Ha et al 2014), which cannot be measured using the interdecadal time scale. The interdecadal change in TC activity in other periods, such as the increase in TC activity in the ENP during 1976-1977 and the increase in TC activity in the WNP during the late 1980s, might be attributable to other processes not currently under investigation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Overall, the characteristics of MCS spatial distribution are similar to the results derived from an investigation of frequency of 2528C IR temperature at each grid over East Asia in Zheng et al (2008), excluding the high-frequency center over the western North Pacific shown in that work. This difference can be explained by a large number of typhoons with active spiral rainbands that occur over the western North Pacific (e.g., Ha et al 2013Ha et al , 2014Ma et al 2015) and eventual boundary systems near the bottom boundary of the domain, all excluded in this study. Figure 4 shows the spatial distribution of the initiation locations for the six MCS types investigated in this study.…”
Section: A Spatial Distributionmentioning
confidence: 99%
“…Temporal variability of the SCS TC genesis from intraseasonal to interdecadal time scales has been noticed (e.g., Ha et al, ; Ha & Zhong, ; Hsu et al, ; Li & Zhou, , ; Li & Zhou, ; Wang et al, ; Wang et al, ). Previous studies revealed that various mechanisms account for the multitemporal variability of TC genesis in the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…The interannual variability of TC genesis in the SCS is primarily related to El Niño–Southern oscillation (Wang et al, ; Wang & Chan, ; Zuki & Lupo, ). Many factors are proposed to be responsible for interdecadal variability of SCS TC genesis frequency (TCGF) in summer, including the Pacific decadal oscillation (Goh & Chan, ), the East Asian summer monsoon and the western Pacific subtropical high (WPSH; Wang et al, ), the eastern Indian Ocean sea surface temperature (SST; Wang, Huang, & Wu, ), the zonal SST gradient between the northern Indian Ocean (NIO) and the WNP (Li & Zhou, ), and the atmospheric intraseasonal variability (ISV) over the SCS (Ha et al, ; Ha & Zhong, ; Ling et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation